Quality evaluation of the measurement of total carbon in soil by an inter-comparison assay. - Guerrero Peña, Armando; Jarquín Sánchez, Aarón; Etchevers Barra, Jorge D.; González Acuña, Irma J.; Hernández Nataren, Lorena del Carmen; Cueto Wong, José A.; Báez Pérez, Aurelio; Hidalgo Moreno, Claudia I.; López Anaya, Miguel A.; Martínez Vargas, Margarita (REVISTA TERRA LATINOAMERICANA, 2019)
The Mexican regulation NMX-EC-17025-IMNC-2006, establishes that laboratories must have quality control procedures to monitor the validity of tests and calibrations, such monitoring must be planned and reviewed with: a) the regular use of certif ied reference materials or internal quality control of secondary references; b) participation in inter-laboratory comparisons or a prof iciency testing program; c) the repetition of tests or calibrations using the same method or different methods; d) the repetition of the test or the calibration of determined objects; e) the correlation of results for different characteristics of a reference material certif ied by MRC. The quality evaluation of results from the eight laboratories of the Laboratory Network for Analysis, Use, Conservation and Management of Soil (REDLABS) included the elements of sections a), b), c), and d) in order to verify the hypothesis that laboratories emit repeatable, reproducible and unbiased results. In our study, elemental analyzers of different brands were used to measure the total carbon of soil. A certif ied reference material was included in the Inter-comparison Practice. Repeatability and reproducibility of the carbon analyzes were evaluated with samples from the inter-comparison practice; the precision of analyzes from each laboratory was qualif ied with MRC. The results obtained indicate that the laboratories show repeatability in their analyzes with no statistical differences, i.e. reproducibility is detected by inter-comparison. The data issued by the laboratories were unbiased according to their evaluation with certif ied reference material.